Understanding and predicting physiological performance of organisms in fluctuating and multifactorial environments. Issue 2 (13th March 2017) - Koussoroplis, Apostolos‐Manuel; Pincebourde, Sylvain; Wacker, Alexander
Abstract: Understanding how variance in environmental factors affects physiological performance, population growth, and persistence is central in ecology. Despite recent interest in the effects of variance in single biological drivers, such as temperature, we have lacked a comprehensive framework for predicting how the variances and covariances between multiple environmental factors will affect physiological rates. Here, we integrate current theory on variance effects with co‐limitation theory into a single unified conceptual framework that has general applicability. We show how the framework can be applied (1) to generate mathematically tractable predictions of the physiological effects of multiple fluctuating co‐limiting factors, (2) to understand how each co‐limiting factor contributes to these effects, and (3) to detect mechanisms such as acclimation or physiological stress when they are at play. We show that the statistical covariance of co‐limiting factors, which has not been considered before, can be a strong driver of physiological performance in various ecological contexts. Our framework can provide powerful insights on how the global change‐induced shifts in multiple environmental factors affect the physiological performance of organisms.